Compliments and positive assessments sequential organization in multi-party conversations - Strubel-Burgdorf, Susanne (Pragmatics & beyond, 2018)
Compliments are among the most widely studied speech acts in pragmatics. The present study takes a new sequential approach by investigating compliments in context, considering compliment form, as part of a Positive Remark continuum, with the respective Response Strategy uttered in response. Analyzed quantitatively and qualitatively in multi-party conversations of the Santa Barbara Corpus of American English, the sequences suggest a connection between the address and reference terms in the Positive Remarks and the strategies chosen as a response.